2017
DOI: 10.1002/cb.1693
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability‐age dilemma: A theory of (un)planned behaviour via influencers

Abstract: This study investigates the relation between age and sustainability awareness for consumers via the third, mediating variable of influencers to reduce the intention-behaviour purchase gap. It proposes that traditional theories of planned behaviour are limited as they do not account for unconscious and indirect pathways to axiological change. A structural model with the 3 constructs of age, influencers, and sustainability awareness is tested with linear structural relations on a sample of 788 consumers, complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 75 publications
(129 reference statements)
1
73
2
Order By: Relevance
“…As noted, there is a widespread environmental deterioration/degradation. The harmful consequences are evident (Hahnel et al, ) and have become a fundamental and a critical social issue (Johnstone & Lindh, ). A serious threat to human survival facing current and future generations has emerged (Dagher & Itani, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted, there is a widespread environmental deterioration/degradation. The harmful consequences are evident (Hahnel et al, ) and have become a fundamental and a critical social issue (Johnstone & Lindh, ). A serious threat to human survival facing current and future generations has emerged (Dagher & Itani, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Second, this research adds to the stream of research on green consumption and marketing and specifically to the study of the driving forces of purchase intention and behavior (e.g., Dagher & Itani, ; Hahnel et al, ; Schuitema & De Groot, ). In light of the redundancy of the traditional green consumer behavior models (Johnstone & Lindh, ), the current research provides a unique perspective by looking at the important aspect of why consumers take into account temporally distant consequences such as the anxiety of death to determine their green consumption (van Dam & Fischer, ).…”
Section: Conclusion Research Implications and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Various researchers have highlighted certain limitations of TPB and TRA and proposed various other frameworks to study consumer sustainable behavior. Johnstone and Lindh [9] suggested that applications of TRA and TPB are restricted as TPB doesn't represent oblivious and secondary pathways to axiological change. Also, TPB and TRA do not consider behavioral aspects such as consumer past behavior and habits [10].…”
Section: Literature Reviewmentioning
confidence: 99%